Polishing Pads
The use of a solid polymer electrolyte-impregnated polishing pad with voltage application and water contact enables efficient and damage-reduced polishing of GaN substrates, overcoming the challenges of existing methods by achieving a practical polishing rate in a neutral environment.
Patent Information
- Application Number
- JP2021022970
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-19
- Filing Date
- 2021-02-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-02-17
AI Technical Summary
Existing methods for polishing conductive semiconductor substrates like gallium nitride (GaN) face challenges in achieving a practical polishing rate while minimizing surface damage, due to the chemical and mechanical stability of GaN.
A polishing pad with a polishing surface impregnated with a solid polymer electrolyte, such as Nafion, is used in conjunction with a voltage application and water contact to generate OH radicals, facilitating oxidation and removal of the substrate surface without requiring strong oxidizing agents.
This method allows for effective polishing of GaN substrates with reduced surface damage, achieving a polishing rate of 100 nm/h or more while maintaining the surface in a neutral region, thus reducing corrosion and operational costs.
Smart Images

Figure 0007654419000001 
Figure 0007654419000002 
Figure 0007654419000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing pad and a method for manufacturing a conductive semiconductor substrate. [Background technology]
[0002] Various methods for polishing the surface of conductive semiconductor substrates such as gallium nitride (GaN) substrates and silicon carbide (SiC) substrates have been disclosed. For example, Patent Document 1 discloses a catalyst-referred etching (CARE) method that uses a catalyst such as platinum to promote an etching reaction. Patent Document 2 discloses a chemical mechanical polishing (CMP) method that uses an oxidizing polishing liquid. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-114632 A [Patent Document 2] International Publication No. 2015 / 152021 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a technique capable of polishing a conductive semiconductor substrate while suppressing damage to the surface of the substrate. [Means for solving the problem]
[0005] According to one aspect of the present invention, A polishing pad used for polishing a surface of a conductive semiconductor substrate, comprising: There is provided a polishing pad, the polishing surface which comes into contact with the surface to be polished being impregnated with at least a solid polymer electrolyte.
[0006] According to another aspect of the present invention, A step of preparing a polishing pad, the polishing surface of which contacts the surface to be polished of the conductive semiconductor substrate being impregnated with at least a solid polymer electrolyte; a step of bringing the polishing surface of the polishing pad into contact with the surface to be polished of the conductive semiconductor substrate under pressure while water molecules are in contact with the solid polymer electrolyte, and polishing the surface to be polished by moving the polishing pad and the conductive semiconductor substrate relative to each other while applying a voltage between the polishing pad and the conductive semiconductor substrate; A method for manufacturing a conductive semiconductor substrate is provided, comprising: Effect of the Invention
[0007] According to the present invention, polishing can be performed while suppressing damage to the surface of a conductive semiconductor substrate. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a plan view illustrating an example of a polishing surface 13 of a polishing pad 10 according to a first embodiment of the present invention. [Diagram 2] Fig. 2(a) is an enlarged schematic view of the polishing surface 13 when a nonwoven fabric is used as the substrate of the polishing pad 10 of the first embodiment of the present invention. Fig. 2(b) is an enlarged schematic view of the polishing surface 13 when a substrate having an open-cell structure is used in the polishing pad 10 of the first embodiment of the present invention. [Diagram 3] FIG. 3 is a plan view diagrammatically illustrating another example of the polishing surface 13 of the polishing pad 10 according to the first embodiment of the present invention. [Figure 4] FIG. 4 is an enlarged schematic view of the polishing surface 13 of the polishing pad 10 according to the first embodiment of the present invention, in which abrasive grains 32 are dispersed on the polishing surface 13. As shown in FIG. [Diagram 5] FIG. 5 is a schematic diagram of a polishing apparatus used in the first embodiment of the present invention. [Figure 6] FIG. 6 is a flowchart showing an example of a method for manufacturing the conductive semiconductor substrate according to the first embodiment of the present invention. [Figure 7]Fig. 7(a) is a cross-sectional view showing a polished surface 14 of a GaN substrate 20 in a preparation step S100 according to the first embodiment of the present invention. Fig. 7(b) is a cross-sectional view showing a polished surface 14 of a GaN substrate 20 and a polished surface 13 of a polishing pad 10 in an oxidation step S111 according to the first embodiment of the present invention. Fig. 7(c) is a cross-sectional view showing a polished surface 14 of a GaN substrate 20 and a polished surface 13 of a polishing pad 10 in a removal step S112 according to the first embodiment of the present invention. [Figure 8] FIG. 8 is a graph showing a schematic diagram of a current flowing through the polishing pad 10 in the polishing step S110 of the first embodiment of the present invention. [Figure 9] FIG. 9 is a cross-sectional photograph of the vicinity of polished surface 14 of GaN substrate 20 in polishing step S110 of the first embodiment of the present invention. [Figure 10] 10(a) and 10(b) are plan views that typically show the polishing surface 13 of a polishing pad 40 according to a second embodiment of the present invention. [Figure 11] FIG. 11 is a graph showing a schematic diagram of a current flowing through the polishing pad 40 in the polishing step S110 of the second embodiment of the present invention. [Figure 12] FIG. 12 is a graph showing the amount of polishing according to the first embodiment of the present invention. [Figure 13] FIG. 13 is a diagram showing the arithmetic mean roughness Ra before and after polishing according to Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] <Inventor's findings> First, the findings of the inventors will be described.
[0010] Various methods have been disclosed for polishing the surface of conductive semiconductor substrates such as GaN substrates and SiC substrates. However, since group III nitrides such as GaN are chemically and mechanically more stable than silicon (Si), which is widely used in semiconductor devices, it is very difficult to polish the surface of a GaN substrate at a practical polishing rate (e.g., 100 nm / h or more).
[0011] The modified Mohs hardness of GaN is 13, which is the second hardest after diamond. This means that when mechanically polishing the surface of a GaN substrate, it is necessary to use hard abrasives such as diamond abrasives, which may cause damage to the substrate surface. In addition, the use of diamond abrasives increases the polishing cost.
[0012] In addition, the surface of a GaN substrate, especially the +c plane, is chemically very stable, so to chemically modify it using a chemical solution, it is necessary to use a strong oxidizing agent such as potassium permanganate. Therefore, when polishing the surface of a GaN substrate by CMP, there are problems in that the components constituting the polishing device are corroded by the oxidizing agent, and the polishing costs are high.
[0013] The inventors of the present application have conducted extensive research into the above-mentioned phenomenon. As a result, they have found that by using a polishing pad whose polishing surface is impregnated with at least a solid polymer electrolyte, it is possible to perform polishing while suppressing damage to the surface of a conductive semiconductor substrate. In the following embodiment of the present invention, there is also the advantage that polishing can be performed in a neutral region since there is no need to use a special oxidizing agent or the like.
[0014] [Details of the embodiment of the present invention] Next, an embodiment of the present invention will be described below with reference to the drawings. Note that the present invention is not limited to these examples, but is defined by the claims, and is intended to include all modifications within the meaning and scope of the claims.
[0015] First embodiment of the present invention (1) Configuration of the polishing pad 10 First, a description will be given of the configuration of a polishing pad 10 of this embodiment. In this embodiment, a case will be described in which the polishing pad 10 is used to polish a surface (hereinafter, also referred to as a polished surface 14) of a GaN substrate 20 serving as a conductive semiconductor substrate.
[0016] The polishing pad 10 is, for example, disk-shaped and is used to polish the polished surface 14 of the GaN substrate 20 as a conductive semiconductor substrate. The base material of the polishing pad 10 may be nonwoven fabric, urethane resin, epoxy resin, suede, or the like. From the viewpoint of ensuring the sliding property with respect to the polished surface 14, it is preferable to use nonwoven fabric as the base material of the polishing pad 10. From the viewpoint of ensuring the conductivity in the thickness direction of the polishing pad 10, it is preferable to use nonwoven fabric or a base material having an open cell structure as the base material of the polishing pad 10. In this specification, the surface of the main surface of the polishing pad 10 that contacts the polished surface 14 of the GaN substrate 20 is referred to as the "polishing surface 13", and the surface opposite to the polishing surface 13 is referred to as the "back surface".
[0017] The diameter of the polishing pad 10 is preferably, for example, 200 mm or more and 2000 mm or less. This allows polishing of the surface 14 to be polished of the GaN substrate 20 having a large diameter (for example, 4 inches or more). The thickness of the polishing pad 10 is preferably, for example, 0.5 mm or more and 10 mm or less. If the thickness of the polishing pad 10 is less than 0.5 mm, the durability of the polishing pad 10 may decrease. In contrast, by setting the thickness of the polishing pad 10 to 0.5 mm or more, the durability of the polishing pad 10 can be improved. On the other hand, if the thickness of the polishing pad 10 exceeds 10 mm, the conductivity of the polishing pad 10 in the thickness direction may decrease. In contrast, by setting the thickness of the polishing pad 10 to 10 mm or less, the conductivity of the polishing pad 10 in the thickness direction can be improved.
[0018] FIG. 1 is a plan view showing an example of the polishing surface 13 of the polishing pad 10 of this embodiment. The polishing pad 10 of this embodiment has at least a solid polymer electrolyte (Solid Polymer Electrolyte, SPE) impregnated into the polishing surface 13. In this embodiment, the solid polymer electrolyte is attached to the substrate surface of the polishing pad 10 (or at least a part of the substrate surface is coated) by impregnation (i.e., by impregnating the substrate of the polishing pad 10 with a liquid material containing the solid polymer electrolyte, evaporating the liquid, and leaving the solid polymer electrolyte in the polishing pad 10). In this specification, the solid polymer electrolyte being attached to the substrate surface of the polishing pad 10 (or at least a part of the substrate surface is coated) is referred to as the polishing pad 10 being impregnated with the solid polymer electrolyte.
[0019] As the solid polymer electrolyte, for example, Nafion (registered trademark, chemical formula: CHF) is a polymer having a fluorocarbon skeleton and a fluorocarbon ether side chain having a sulfonic acid group at the end. 13 O5S·C2F4) can be used. That is, the polishing surface 13 is impregnated with Nafion 15 as a solid polymer electrolyte. Note that Nafion 15 is omitted in FIG. 1. For example, Nafion 15 can generate OH radicals from water by applying a voltage. By generating OH radicals, the polishing surface 14 of the GaN substrate 20 can be oxidized. Gallium oxide (Ga2O3) generated by oxidizing the GaN 30 constituting the polishing surface 14 is softer than the GaN 30. Therefore, the gallium oxide generated by oxidizing the polishing surface 14 of the GaN substrate 20 can be removed more easily than the GaN 30. Note that in this specification, the oxidation of the GaN 30 constituting the polishing surface 14 of the GaN substrate 20 is also referred to as oxidizing the polishing surface 14 of the GaN substrate 20 to avoid complication.
[0020] It is preferable that Nafion 15 is also impregnated in the thickness direction of the polishing pad 10. Since Nafion 15 has ion conductivity, it is possible to ensure ion conductivity in the thickness direction of the polishing pad 10. Furthermore, since Nafion 15 exhibits electrical conductivity in the presence of water, it is preferable that electrical conduction is established between the polishing surface 13 and the back surface at least in a state where water molecules are in contact with Nafion 15.
[0021] In the polishing pad 10, Nafion 15 is, for example, 3 mg / cm 3 More than 20mg / cm 3 It is preferable that the density of Nafion 15 is 3 mg / cm 3 If the density of Nafion 15 is less than 3 mg / cm, it is difficult to obtain the effect of oxidizing the polished surface 14. 3 By setting the density of the Nafion 15 at 20 mg / cm or more, the polished surface 14 can be easily oxidized. 3 If the density of Nafion 15 is more than 20 mg / cm, the flexibility of the polishing pad 10 decreases, and the polished surface 14 may be scratched during polishing. 3 By setting the density as below, the flexibility of the polishing pad 10 is maintained, and the possibility of scratching the polished surface 14 during polishing can be reduced. In this specification, the density of Nafion 15 is a value obtained by dividing the mass of Nafion 15 contained in the polishing pad 10 by the apparent volume of the polishing pad 10 (volume including internal voids).
[0022] FIG. 2(a) is an enlarged schematic diagram of the polishing surface 13 when a nonwoven fabric is used as the base material of the polishing pad 10. As shown in FIG. 2(a), Nafion 15 is preferably attached to the surface of the fibers 16 of the nonwoven fabric (or at least a part of the surface is coated). In general, a Nafion film is not suitable as a base material of the polishing pad 10 because of its poor sliding property against the GaN substrate 20. In contrast, in this embodiment, since Nafion 15 is attached to the surface of the fibers 16 of the nonwoven fabric, the sliding property against the polished surface 14 can be improved compared to the case where a Nafion film is used for the polishing pad 10. In order to confirm that Nafion 15 is attached to the surface of the fibers 16, for example, the fibers 16 are cut and the vicinity of the cross section of the fibers 16 is measured using energy dispersive X-ray analysis (EDX) to check whether fluorine (F) is detected.
[0023] It is preferable that Nafion 15 exists so as to connect a plurality of fibers 16. As a result, Nafion 15 is connected in the polishing pad 10, so that the electrical conductivity of the polishing pad 10 can be improved. Also, FIG. 2(b) is an enlarged schematic diagram of the polishing surface 13 when a base material having an open-cell structure is used for the polishing pad 10. In this case, too, as shown in FIG. 2(b), Nafion 15 covering the inside of the cells 17 is connected, so that the electrical conductivity of the polishing pad 10 can be improved.
[0024] 3 is a plan view showing another example of the polishing surface 13 of the polishing pad 10 of the present embodiment. As shown in FIG. 3, abrasive grains 32 may be dispersed on the polishing surface 13. This makes it possible to remove oxides 31 (e.g., gallium oxide) generated by oxidizing GaN 30 constituting the polished surface 14 of the GaN substrate 20 with OH radicals. In this case, it is preferable that the abrasive grains 32 are also impregnated in the thickness direction of the polishing pad 10. This makes it possible to maintain the polishing rate even if the polishing surface 13 is worn during polishing.
[0025] The abrasive grains 32 are preferably lower in hardness than the GaN 30 constituting the polished surface 14 of the GaN substrate 20. Examples of such abrasive grains 32 include cerium oxide (CeO2), silicon oxide (SiO2), and zirconium oxide (ZrO2). Normally, in mechanical polishing, abrasive grains harder than the object to be polished are used, but in this embodiment, since only the oxide 31 is removed, the polished surface 14 of the GaN substrate 20 can be polished even with abrasive grains 32 softer than the GaN 30. As a result, it is possible to perform polishing while suppressing damage to the polished surface 14 of the GaN substrate 20. Note that, although there are Vickers hardness and Knoop hardness as scales for expressing hardness, it is important that the scale of hardness can simply express the resistance to scratches. Therefore, it is preferable to use Mohs hardness or modified Mohs hardness as the scale of hardness.
[0026] When cerium oxide having an average particle size (D50) of about 1 μm (for example, 0.5 μm or more and 2 μm or less) as determined by a laser diffraction / scattering method is used as the abrasive grains 32, the abrasive grains 32 in the polishing pad 10 have a density of, for example, 0.1 g / cm 3 More than 0.5g / cm 3 It is preferable that the density of the abrasive grains 32 is 0.1 g / cm 3 If the density of the abrasive grains 32 is less than 0.1 mg / cm3, it is difficult to obtain the effect of removing the oxides 31. 3 By setting the density of the abrasive grains 32 at 0.5 g / cm or more, it becomes easier to remove the oxides 31. 3 When manufacturing a polishing pad 10 having a density exceeding 0.5 g / cm, the viscosity of the dispersion liquid becomes too high when the polishing pad 10 is impregnated with the dispersion liquid of the abrasive grains 32, so there is a possibility that the dispersion liquid cannot be impregnated into the polishing pad 10. 3 The above makes it easier to impregnate the polishing pad 10 with a dispersion of the abrasive grains 32. In this specification, the density of the abrasive grains 32 is the value obtained by dividing the mass of the abrasive grains 32 contained in the polishing pad 10 by the apparent volume of the polishing pad 10 (volume including internal voids).
[0027] Fig. 4 is an enlarged schematic diagram of the polishing surface 13 when abrasive grains 32 are dispersed on the polishing surface 13. As shown in Fig. 4, Nafion 15 is preferably attached also to the surfaces of the abrasive grains 32. This can improve the electrical conductivity of the polishing pad 10.
[0028] When the abrasive grains 32 are not dispersed on the polishing surface 13, for example, in the polishing step S110 described below, polishing may be performed while supplying a slurry containing the abrasive grains 32 to the polishing surface 13. In this case, it is possible to reduce the risk of the polishing rate decreasing due to the abrasive grains 32 falling off the polishing pad 10. From the viewpoint of reducing the consumption of the abrasive grains 32, it is preferable that the abrasive grains 32 are dispersed on the polishing surface 13 in advance.
[0029] It is preferable that the polishing pad 10 has water retention. This allows OH radicals to be efficiently generated from water. In addition, since Nafion 15 exhibits electrical conductivity in the presence of water, the electrical conductivity of the polishing pad 10 can be improved. Specifically, for example, the water retention of the polishing pad 10 can be improved by dispersing a small amount of water-absorbing polymer in the polishing pad 10.
[0030] It is preferable that polishing surface 13 of polishing pad 10 has a sliding property with respect to, for example, polished surface 14 of GaN substrate 20. This makes it easier to move polishing pad 10 and GaN substrate 20 relative to each other while keeping them in contact with each other.
[0031] The back surface of the polishing pad 10 preferably has a conductive adhesive. Alternatively, a conductive aluminum tape or the like may be used instead of the conductive adhesive. This ensures conductivity between the platen 21 and the polishing pad 10 when the polishing pad 10 is attached onto the platen 21 described below.
[0032] (2) Manufacturing method of polishing pad 10 Next, a method for manufacturing the polishing pad 10 of this embodiment will be described. In this embodiment, a nonwoven fabric is used as the base material of the polishing pad 10, and the polishing surface 13 is impregnated with Nafion 15 as a solid polymer electrolyte and cerium oxide is dispersed as the abrasive grains 32. In this embodiment, since the nonwoven fabric is used as the base material of the polishing pad 10, Nafion 15 can be easily impregnated in the thickness direction of the polishing pad 10, and the abrasive grains 32 can be easily dispersed.
[0033] First, the nonwoven fabric is impregnated with a cerium oxide dispersion (e.g., 60% by weight, average particle size (D50) 1 μm). It is preferable to add a small amount of sodium alginate (e.g., 0.25% by weight) to the cerium oxide dispersion. This increases the viscosity of the cerium oxide dispersion, making it easier to disperse cerium oxide in the polishing pad 10 (on the polishing surface 13 and in the thickness direction of the polishing pad 10).
[0034] After impregnating the nonwoven fabric with the cerium oxide dispersion, it is preferable to place the nonwoven fabric in an aqueous calcium chloride solution (e.g., 20% by weight), which causes sodium alginate and calcium chloride to react and gel, making it easier to disperse cerium oxide in the polishing pad 10.
[0035] Furthermore, rare earth oxides such as praseodymium oxide, neodymium oxide, and lanthanum oxide may be added to the cerium oxide dispersion liquid. This makes it easier for the abrasive grains 32 to remove the oxides 31.
[0036] After the nonwoven fabric is impregnated with the cerium oxide dispersion, excess cerium oxide dispersion is removed using, for example, a squeezer, and then the fabric is dried at 70° C. for 30 minutes using a constant temperature dryer, etc. In this manner, cerium oxide as abrasive grains 32 can be dispersed on the polishing surface 13.
[0037] Next, the nonwoven fabric is impregnated with a Nafion dispersion (5 to 20% by weight, for example, it is preferable to use any one of product numbers 274704, 527084, 510211, 527106, 663492, and 527122 manufactured by Sigma-Aldrich).
[0038] After the nonwoven fabric is impregnated with the Nafion dispersion, excess Nafion dispersion is removed using, for example, a squeezer, and then the nonwoven fabric impregnated with the Nafion dispersion is dried for 30 minutes at 70° C. using a constant temperature dryer, etc. In this manner, the polishing surface 13 can be impregnated with Nafion 15. The impregnation with the Nafion dispersion and drying may be repeated several times.
[0039] By using a Nafion dispersion liquid when impregnating the nonwoven fabric with Nafion 15, the sliding properties of the polishing pad 10 can be improved compared to the case where a Nafion film is used. As a result, the polishing pad 10 and the GaN substrate 20 can be easily moved relative to each other while being in contact with each other, and the polished surface 14 of the GaN substrate 20 can be polished efficiently.
[0040] In this manner, a polishing pad 10 can be obtained in which the polishing surface 13 is impregnated with Nafion 15 and has abrasive grains 32 dispersed therein. It is preferable to first disperse the abrasive grains 32 in the nonwoven fabric and then impregnate the nonwoven fabric with Nafion 15. In this case, Nafion 15 is easily attached to the surface of the abrasive grains 32, and therefore the electrical conductivity of the polishing pad 10 can be improved.
[0041] (3) Polishing Equipment Configuration Next, the configuration of the polishing apparatus used in this embodiment will be described. Fig. 5 is a schematic diagram of the polishing apparatus used in this embodiment. As shown in Fig. 5, the polishing apparatus of this embodiment has, for example, a surface plate 21, a substrate holder 22, a power source 23, and a pure water supply unit 24. Note that Nafion 15 impregnated in the polishing surface 13 and abrasive grains 32 dispersed on the polishing surface 13 are omitted in Fig. 5.
[0042] The surface plate 21 is, for example, a stainless steel disk, and is configured so that the polishing pad 10 is attached to the upper surface. The surface plate 21 is configured to rotate at a predetermined rotation speed in the horizontal direction with the polishing pad 10 attached to the upper surface. Note that the surface plate 21 is not limited to being made of stainless steel, and may be made of any material that is conductive and rigid.
[0043] The substrate holder 22 is made of, for example, stainless steel, and is configured to attach the GaN substrate 20 to its bottom surface. The GaN substrate 20 is preferably attached to the substrate holder 22 using, for example, a conductive adhesive, with the polished surface 14 exposed. That is, it is preferable to electrically connect the back surface of the GaN substrate 20 (the surface opposite to the polished surface 14) to the substrate holder 22. This allows the polished surface 14 of the GaN substrate 20 to be entirely exposed, and the entire polished surface 14 can be polished.
[0044] The substrate holder 22 is configured to rotate at a predetermined rotation speed in the horizontal direction with the GaN substrate 20 attached to the bottom surface. The substrate holder 22 is also configured to press the polished surface 14 of the GaN substrate 20 against the polishing surface 13 of the polishing pad 10 with a predetermined pressure. The substrate holder 22 is not limited to being made of stainless steel, and may be made of any material that is conductive and rigid.
[0045] The power supply 23 is electrically connected to, for example, the platen 21 and the substrate holder 22, and is configured to apply a predetermined voltage to the polishing pad 10. The power supply 23 is configured so that the substrate holder 22 side (GaN substrate 20 side) serves as the anode. When the power supply 23 applies a voltage to the polishing pad 10, OH radicals can be generated from water on the surface of the Nafion 15 impregnated in the polishing surface 13. As the power supply 23, for example, a combination of a commercially available potentiostat and a function generator can be used.
[0046] The pure water supply unit 24 is configured to supply pure water to the polishing surface 13 of the polishing pad 10, for example, in the form of a spray. The pure water supply unit 24 supplies pure water to the polishing surface 13, thereby improving the electrical conductivity of the polishing pad 10. In addition, OH radicals can be generated from the water on the surface of the Nafion 15. Furthermore, the oxides 31 removed from the polished surface 14 of the GaN substrate 20 can be discharged from the polishing surface 13. In this specification, pure water means, for example, water having a resistivity of 0.1 MΩ·cm or more and 18 MΩ·cm or less.
[0047] (4) Method for manufacturing a conductive semiconductor substrate Next, a method for manufacturing a conductive semiconductor substrate using the polishing pad 10 of this embodiment will be described. FIG. 6 is a flow chart showing an example of a method for manufacturing a conductive semiconductor substrate of this embodiment. As shown in FIG. 6, the method for manufacturing a conductive semiconductor substrate of this embodiment includes, for example, a preparation step S100, an oxidation step S111, and a removal step S112. The oxidation step S111 and the removal step S112 are also collectively referred to as a polishing step S110. In this embodiment, a case will be described in which the polished surface 14 of a GaN substrate 20 is polished using the polishing pad 10 to manufacture a GaN substrate 20 having a polished surface.
[0048] (Preparation step S100) In the preparation step S100, a polishing pad 10 and a GaN substrate 20 as a conductive semiconductor substrate are prepared. The GaN substrate 20 is, for example, a disk-shaped free-standing substrate made of a single crystal of GaN. The diameter of the GaN substrate 20 is, for example, 2 inches to 6 inches. The thickness of the GaN substrate 20 is, for example, 0.25 mm or more. Such a GaN substrate 20 is obtained by slicing a GaN crystal epitaxially grown by, for example, HVPE (hydride vapor phase epitaxy). The polished surface 14 of the GaN substrate 20 is, for example, a +c plane, and is an as-sliced surface, so that the polished surface 14 needs to be polished in order to use the GaN substrate 20 in the manufacture of a semiconductor device or the like. In this specification, the "+c plane" includes a plane slightly inclined (for example, at an off angle of 5° or less) from the (0001) plane of the GaN crystal.
[0049] Fig. 7(a) is a cross-sectional view showing the polished surface 14 of the GaN substrate 20 in the preparation step S100 of this embodiment. Fig. 7(b) is a cross-sectional view showing the polished surface 14 of the GaN substrate 20 and the polished surface 13 of the polishing pad 10 in the oxidation step S111 of this embodiment. Fig. 7(c) is a cross-sectional view showing the polished surface 14 of the GaN substrate 20 and the polished surface 13 of the polishing pad 10 in the removal step S112 of this embodiment. As shown in Fig. 7(a), the polished surface 14 of the GaN substrate 20 in the preparation step S100 is made of GaN 30, and has many irregularities because it is an as-sliced surface.
[0050] The carrier concentration of the polished surface 14 of the GaN substrate 20 is, for example, 1.0×10 16 cm -3 It is preferable that the carrier concentration is equal to or higher than 1.0×10. This ensures electrical conductivity in the thickness direction of the GaN substrate 20. The upper limit of the carrier concentration of the polished surface 14 of the GaN substrate 20 is not particularly limited, but is preferably 1.0×10 20 cm -3 The following is an example:
[0051] (Polishing process S110) In the polishing step S110, for example, polishing pad 10 and the above-mentioned polishing apparatus are used to polish surface 14 of GaN substrate 20. First, polishing pad 10 is attached to platen 21 so that polishing surface 13 is exposed, and GaN substrate 20 is attached to substrate holder 22 so that polishing surface 14 is exposed.
[0052] In the polishing step S110, with water molecules in contact with Nafion 15, polishing surface 13 of polishing pad 10 is brought into contact with polished surface 14 of GaN substrate 20 under pressure, and polishing pad 10 and GaN substrate 20 are moved relative to each other while a voltage is applied between them, thereby polishing surface 14.
[0053] In the polishing step S110, the surface 14 to be polished of the GaN substrate 20 is pressed against the polishing surface 13 of the polishing pad 10 with a predetermined pressure. The pressure (polishing pressure) at which the surface 14 to be polished of the GaN substrate 20 is pressed against the polishing surface 13 is preferably, for example, 10 kPa or more and 100 kPa or less. Moreover, it is preferable to press the surface 14 to be polished of the GaN substrate 20 so that pressure is applied uniformly to the surface 14 to be polished of the GaN substrate 20. This makes it possible to polish the surface 14 to be polished of the GaN substrate 20 uniformly in-plane.
[0054] In the polishing step S110, a predetermined voltage is applied to the polishing pad 10 using a power source 23 while the polished surface 14 of the GaN substrate 20 is pressed against the polishing surface 13 of the polishing pad 10 with a predetermined pressure, thereby oxidizing the polished surface 14. The power source 23 is electrically connected to the substrate holder 22, the GaN substrate 20, the polishing pad 10, and the platen 21, for example, in this order from the anode side.
[0055] The voltage applied by the power supply 23 is preferably 20V or more and 300V or less. If the voltage applied by the power supply 23 is less than 20V, it is difficult to generate OH radicals from water on the surface of the Nafion 15 impregnated in the polishing surface 13. In contrast, if the voltage applied by the power supply 23 is 20V or more, it is easy to generate OH radicals. On the other hand, if the voltage applied by the power supply 23 exceeds 300V, the polishing surface 14 of the GaN substrate 20 may become rough. In contrast, if the voltage applied by the power supply 23 is 300V or less, the polishing surface 14 of the GaN substrate 20 can be polished smoothly and at an appropriate polishing rate.
[0056] The polishing rate varies depending on the voltage V applied by the power source 23, and there are cases where the polishing rate becomes maximum (maximum) at a certain voltage Vm (for example, when polishing a SiC substrate as a conductive semiconductor substrate). In this case, it is preferable to control the voltage V applied by the power source 23 so as not to exceed the voltage Vm at which the polishing rate becomes maximum (maximum). If the voltage V exceeds the voltage Vm, the removal of the oxide 31 becomes rate-limiting, and the polished surface 14 may become rough. In contrast, by controlling the voltage V so as not to exceed the voltage Vm, the polished surface 14 can be polished smoothly and at an appropriate polishing rate.
[0057] In the polishing step S110, the surface plate 21 and the substrate holder 22 are rotated at a predetermined rotation speed in the horizontal direction while a predetermined voltage is applied to the polishing pad 10. The rotation speed of the surface plate 21 is preferably, for example, 10 rpm or more and 300 rpm or less. The rotation speed of the substrate holder 22 is preferably, for example, 10 rpm or more and 300 rpm or less. The rotation speeds of the surface plate 21 and the substrate holder 22 may be the same or different. The rotation directions of the surface plate 21 and the substrate holder 22 may be the same or different.
[0058] In the polishing step S110, for example, it is preferable to supply pure water to the polishing surface 13 using the pure water supply unit 24. This can improve the conductivity of the polishing pad 10. In addition, it is preferable that the amount of water supplied by the pure water supply unit 24 is, for example, 0.1 mL / min or more and 5 mL / min or less. If the amount of water supplied is less than 0.1 mL / min, the conductivity of the polishing pad 10 may be insufficient. In contrast, by setting the amount of water supplied to 0.1 mL / min or more, the conductivity of the polishing pad 10 can be sufficiently improved. On the other hand, if the amount of water supplied exceeds 5 mL / min or less, the Nafion 15 or the abrasive grains 32 may be washed away by the pure water. In contrast, by setting the amount of water supplied to 5 mL / min or less, the risk of the Nafion 15 or the abrasive grains 32 being washed away by the pure water can be reduced.
[0059] In this embodiment, since only pure water is supplied without using an oxidizing agent such as potassium permanganate, polishing can be performed in a neutral region. In this specification, "polishing in a neutral region" means, for example, performing the polishing step S110 while maintaining the pH of the polishing surface 13 of the polishing pad 10 in a state of 6.0 or more and 8.0 or less. The pH of the polishing surface 13 can be measured, for example, using a pH meter. If necessary, the pH of the polishing surface 13 may be adjusted to be outside the above range.
[0060] In the polishing step S110, it is preferable to supply pure water to the polishing surface 13 so as to keep the humidity of the polishing surface 13 within a certain range (for example, 60% or more and 100% or less). That is, since the value of the current flowing through the polishing pad 10 varies depending on the humidity of the polishing surface 13, it is preferable to monitor the value of the current flowing through the polishing pad 10 using, for example, a digital multimeter, and control the humidity of the polishing surface 13 so that the current value is constant. This makes it possible to stabilize the polishing rate.
[0061] When the polishing pad 10 in which the abrasive grains 32 are not dispersed is used on the polishing surface 13, it is preferable to supply a slurry containing the abrasive grains 32 to the polishing surface 13 in the polishing step S110. This makes it possible to polish the surface 14 to be polished in the same manner as when the polishing pad 10 in which the abrasive grains 32 are dispersed in advance is used. In addition, the risk of a decrease in the polishing rate due to the abrasive grains 32 falling off the polishing pad 10 can be reduced.
[0062] 8 is a graph showing a schematic diagram of a current flowing through the polishing pad 10 in the polishing step S110 of this embodiment. In this embodiment, it is preferable to apply a pulse voltage to the polishing pad 10 using a power source 23, for example, to cause a current to flow intermittently through the polishing pad 10. As shown in FIG. 8, the oxidation step S111 is performed while a current is flowing through the polishing pad 10. On the other hand, the removal step S112 is performed continuously regardless of whether a current is flowing through the polishing pad 10. That is, in this embodiment, the oxidation step S111 and the removal step S112 are performed simultaneously while a current is flowing through the polishing pad 10.
[0063] In this embodiment, the oxidation step S111 and the removal step S112 are performed simultaneously while a current is flowing through the polishing pad 10. This allows the oxide 31 generated on the polished surface 14 of the GaN substrate 20 to be quickly removed by the abrasive grains 32, thereby improving the polishing rate. In addition, the removal step S112 is performed while no current is flowing through the polishing pad 10. At that time, the removed oxide 31 can be discharged from the polishing surface 13 by, for example, pure water supplied to the polishing surface 13 by the pure water supply unit 24.
[0064] In this embodiment, while the polishing pad 10 and the GaN substrate 20 are moved relative to each other while being in contact with each other, the entire surface of the polished surface 14 of the GaN substrate 20 is always in contact with the polishing surface 13 impregnated with Nafion 15. This allows the polished surface 14 of the GaN substrate 20 to be oxidized uniformly within the surface. As a result, the polished surface 14 of the GaN substrate 20 can be polished uniformly within the surface.
[0065] 8, if the pulse period is T and the time during which the current flows in one period is t, the duty ratio D is defined as D=t / T. It is preferable that the duty ratio D is, for example, 1% or more and 100% or less. In this embodiment, by controlling the duty ratio D, the speed at which the polished surface 14 is oxidized can be adjusted, and therefore the polishing rate can be controlled.
[0066] In the polishing step S110, it is preferable that the oxide 31 generated during one cycle of the oxidation step S111 is completely removed before the next oxidation step S111 is performed. In other words, it is preferable to control the current flowing through the polishing pad 10 so that the amount of oxide 31 generated during one cycle of the oxidation step S111 does not exceed the amount of oxide 31 that can be removed during the period T. This allows the polished surface 14 to be polished smoothly and at an appropriate polishing rate.
[0067] (Oxidation step S111) In the oxidation step S111, OH radicals are generated from water on the surface of Nafion 15, and the OH radicals oxidize GaN 30 constituting polished surface 14 of GaN substrate 20. When a current flows through polishing pad 10, OH radicals are generated from water on the surface of Nafion 15 by the reaction shown in the following reaction formula (1).
[0068] HO→OH +H + +e - (1)
[0069] When OH radicals are generated, GaN 30 is oxidized on polished surface 14 of GaN substrate 20 by the reaction shown in reaction formula (2) below, and oxide 31 (here, gallium oxide) is generated.
[0070] 2GaN+6OH·→Ga2O3+N2+3H2O···(2)
[0071] 7(b), in the oxidation step S111, the convex portions of GaN 30 are preferentially oxidized to generate oxides 31. That is, of the polished surface 14 of GaN substrate 20, the portions in contact with (or close to) polished surface 13 are preferentially oxidized. As a result, in the removal step S112 described below, the oxides 31 generated on the convex portions are removed, thereby making it possible to efficiently planarize the polished surface 14 of GaN substrate 20.
[0072] OH radicals usually have a short life span and cannot exist for a long time. However, in the polishing pad 10 of this embodiment, OH radicals are generated on the polishing surface 13 that is in contact with the polished surface 14 of the GaN substrate 20, so that the generation of OH radicals and the oxidation of the polished surface 14 of the GaN substrate 20 can be performed simultaneously. Therefore, the polished surface 14 of the GaN substrate 20 can be oxidized before the OH radicals disappear.
[0073] Furthermore, OH radicals may decompose the side chains of Nafion 15, degrading Nafion 15. However, in the polishing pad 10 of the present embodiment, the generated OH radicals are used to oxidize the polished surface 14 of the GaN substrate 20, so that degradation of Nafion 15 due to OH radicals can be suppressed.
[0074] (Removal step S112) In the removal step S112, the oxide 31 generated by the oxidation of the GaN 30 by the OH radicals is removed. Specifically, for example, as shown in FIG. 7(c), the oxide 31 is mechanically removed by abrasive grains 32 dispersed on the polished surface 13. Since the abrasive grains 32 are lower in hardness than the GaN 30, only the oxide 31 can be removed without scratching the GaN 30. As a result, it becomes possible to polish the polished surface 14 of the GaN substrate 20 while suppressing damage to the polished surface 14 of the GaN substrate 20. In this specification, polishing the polished surface 14 of the GaN substrate 20 means, for example, as shown in FIG. 7(c), scraping off a part of the GaN 30 constituting the polished surface 14 of the GaN substrate 20 to flatten the surface.
[0075] The time for performing the polishing step S110 can be set arbitrarily depending on the application of the GaN substrate 20, etc.
[0076] In the polishing step S110, the surface of the GaN substrate 20 can be planarized by repeatedly performing the above-mentioned oxidation step S111 and removal step S112. The arithmetic mean roughness Ra (see JIS B 0601-2001) of the surface (polished surface) of the GaN substrate 20 after the polishing step S110 is preferably, for example, 0.7 nm or less. This makes the GaN substrate 20 after the polishing step S110 suitable for use in the manufacture of semiconductor devices, etc. The lower limit of the arithmetic mean roughness Ra of the surface of the GaN substrate 20 after the polishing step S110 is not particularly limited, but is, for example, 0.1 nm or more.
[0077] In the polishing step S110, the polished surface 14 of the GaN substrate 20 is efficiently oxidized by highly reactive OH radicals and the oxide 31 is removed to polish the polished surface 14 of the GaN substrate 20, so that the polishing rate can be improved compared to the conventional method. Specifically, the polishing rate in the polishing step S110 can be, for example, 100 nm / h or more and 10,000 nm / h or less. In this specification, the polishing rate means the thickness removed per unit time of polishing.
[0078] FIG. 9 is a cross-sectional photograph of the vicinity of the polished surface 14 of the GaN substrate 20 in the polishing step S110. In the polishing step S110, it is preferable to form a porous structure on the polished surface 14 of the GaN substrate 20, and then remove the porous structure. In this specification, the porous structure means a structure in which a plurality of voids are formed in a crystal. In FIG. 9, a plurality of void layers (porous layers 18) are formed parallel to the polished surface 14. By forming the porous structure, the crystal above it is easier to remove, and therefore the polishing rate can be improved. In addition, the porous structure is easily formed when polishing a conductive semiconductor substrate, particularly a GaN substrate 20.
[0079] When polishing step S110 is to be completed, it is preferable to stop power supply 23 for a predetermined time, and move polishing pad 10 and GaN substrate 20 relatively while in contact with each other in a state where no voltage is applied to polishing pad 10. This makes it possible to complete polishing step S110 in a state where no oxide 31 remains on polished surface 14 of GaN substrate 20. In addition, it is possible to reduce uneven polishing caused by the distribution of the in-plane electrical properties of polished surface 14.
[0080] Through the above steps, a GaN substrate 20 having a polished surface can be manufactured.
[0081] (5) Effects of this embodiment According to this embodiment, one or more of the following advantages are achieved.
[0082] (a) The polishing pad 10 of this embodiment is impregnated with a solid polymer electrolyte for generating OH radicals on the polishing surface 13 and oxidizing the polished surface 14 of the GaN substrate 20 with the OH radicals. Therefore, the polished surface 14 of the GaN substrate 20 can be oxidized. As a result, it is possible to perform polishing while suppressing damage to the polished surface 14 of the GaN substrate 20. In addition, in this embodiment, the polished surface 14 of the GaN substrate 20 is efficiently oxidized by highly reactive OH radicals, so that the polishing rate can be improved compared to the conventional method. Furthermore, in this embodiment, since an oxidizing agent such as potassium permanganate is not used and only pure water is supplied, polishing can be performed in a neutral region.
[0083] (b) In the polishing pad 10 of this embodiment, the polishing surface 13 is impregnated with Nafion 15 as a solid polymer electrolyte that generates OH radicals from water by applying a voltage. Therefore, the generation of OH radicals and the oxidation of the polished surface 14 of the GaN substrate 20 can be performed simultaneously. Therefore, the polished surface 14 of the GaN substrate 20 can be oxidized before the OH radicals disappear. Furthermore, in the polishing pad 10 of this embodiment, the generated OH radicals are used to oxidize the polished surface 14 of the GaN substrate 20, so that the deterioration of the Nafion 15 due to the OH radicals can be suppressed.
[0084] (c) In the polishing pad 10 of this embodiment, abrasive grains 32 for removing oxides 31 are preferably dispersed on the polishing surface 13. In this embodiment, since only oxides 31 are removed, the polished surface 14 of the GaN substrate 20 can be polished even with abrasive grains 32 that are softer than GaN 30. As a result, it is possible to perform polishing while suppressing damage to the polished surface 14 of the GaN substrate 20.
[0085] Second embodiment of the present invention Next, a second embodiment of the present invention will be described, focusing on the differences from the first embodiment. Elements that are substantially the same as those described in the first embodiment will be given the same reference numerals, and the description thereof will be omitted.
[0086] (1) Configuration of the polishing pad 40 10(a) and 10(b) are plan views showing the polishing surface 13 of the polishing pad 40 of the present embodiment. As shown in FIG. 10(a) and FIG. 10(b), the polishing pad 40 of the present embodiment has a first region 11 and a second region 12 on the polishing surface 13. The first region 11 and the second region 12 are, for example, fan-shaped and arranged adjacent to each other. FIG. 10(a) shows an example in which the first region 11 is fan-shaped with a central angle of 90 degrees and the second region 12 is fan-shaped with a central angle of 270 degrees. The arrangement of the first region 11 and the second region 12 is not limited to the above-mentioned embodiment and can be changed in various ways. For example, as shown in FIG. 10(b), the fan-shaped first region 11 and the second region 12 may be arranged so that a plurality of them are alternately adjacent to each other.
[0087] In polishing pad 40 of the present embodiment, first region 11 and second region 12 are arranged so as to alternately come into contact with polished surface 14 of GaN substrate 20 due to relative movement between polishing pad 40 and GaN substrate 20. The effect of this will be described later.
[0088] The first region 11 is a region for generating OH radicals and oxidizing the GaN 30 as a semiconductor crystal constituting the polished surface 14 of the GaN substrate 20 by the OH radicals.
[0089] The first region 11 is impregnated with, for example, Nafion 15 as a solid polymer electrolyte. Moreover, it is preferable that the Nafion 15 is impregnated throughout the entire thickness direction of the polishing pad 40. Since the Nafion 15 has ion conductivity, it is possible to ensure ion conductivity in the thickness direction of the polishing pad 40. Note that the Nafion 15 is omitted in Figures 10(a) and 10(b).
[0090] The second region 12 is a region for removing oxide 31 (e.g., gallium oxide) generated by oxidation of GaN 30 constituting the polished surface 14 of the GaN substrate 20 by OH radicals. Since the polishing pad 40 of the present embodiment has the first region 11 and the second region 12 on the polishing surface 13, it is possible to perform oxidation and removal of oxide 31 on the polished surface 14 of the GaN substrate 20 using one polishing pad 40.
[0091] In the second region 12, for example, abrasive grains 32 for removing oxide 31 are dispersed. The abrasive grains 32 preferably have a lower hardness than the GaN 30 constituting the polished surface 14 of the GaN substrate 20. Examples of such abrasive grains 32 include cerium oxide (CeO2), silicon oxide (SiO2), and zirconium oxide (ZrO2).
[0092] (2) Manufacturing method of the polishing pad 40 First, the nonwoven fabric is impregnated with the Nafion dispersion. At this time, for example, only the first region 11 may be immersed in the Nafion dispersion so that only the first region 11 is impregnated with the Nafion dispersion, or wax or the like may be applied to the portion other than the first region 11. By applying wax or the like to the portion other than the first region 11, only the first region 11 can be impregnated with the Nafion dispersion. The Nafion dispersion may be the same as that used in the first embodiment.
[0093] After the first region 11 is impregnated with the Nafion dispersion, excess Nafion dispersion is removed using, for example, a squeezer, and then the nonwoven fabric impregnated with the Nafion dispersion is dried for 30 minutes at 70° C. using a constant temperature dryer, etc. In this manner, the first region 11 can be impregnated with Nafion 15. The impregnation with the Nafion dispersion and the drying may be repeated multiple times.
[0094] After the first region 11 is impregnated with Nafion 15, the nonwoven fabric is impregnated with the cerium oxide dispersion. At this time, for example, only the second region 12 may be immersed in the cerium oxide dispersion, or wax or the like may be applied to the portion other than the second region 12 so that only the second region 12 is impregnated with the cerium oxide dispersion. By applying wax or the like to the portion other than the second region 12, only the second region 12 can be impregnated with the cerium oxide dispersion. In addition, it is preferable to add a small amount of sodium alginate (for example, 0.25% by weight) to the cerium oxide dispersion. This increases the viscosity of the cerium oxide dispersion, making it easier to disperse cerium oxide in the second region 12. The cerium oxide dispersion may be the same as that used in the first embodiment.
[0095] After the second region 12 is impregnated with the cerium oxide dispersion, it is preferable to place the nonwoven fabric in an aqueous calcium chloride solution (e.g., 20% by weight). This causes sodium alginate and calcium chloride to react and gel, making it easier to disperse cerium oxide in the second region 12.
[0096] Furthermore, rare earth oxides such as praseodymium oxide, neodymium oxide, and lanthanum oxide may be added to the cerium oxide dispersion liquid. This makes it easier for the abrasive grains 32 to remove the oxides 31.
[0097] After the second region 12 is impregnated with the cerium oxide dispersion, excess cerium oxide dispersion is removed using, for example, a squeezer, and then the resulting product is dried for 30 minutes at 70° C. using a constant temperature dryer, etc. In this manner, a polishing pad 40 having the first region 11 and the second region 12 on the polishing surface 13 can be obtained.
[0098] (3) Method for manufacturing a conductive semiconductor substrate In the polishing step S110 of this embodiment, the polishing pad 40 and the GaN substrate 20 are moved relative to each other to alternately bring the first region 11 and the second region 12 into contact with the polished surface 14 of the GaN substrate 20. Specifically, for example, the GaN substrate 20 is arranged so that the center of the polished surface 14 is located at a position radially away from the center of the polished surface 13 at a predetermined distance, and the platen 21 is rotated horizontally at a predetermined rotation speed to alternately bring the first region 11 and the second region 12 into contact with the polished surface 14 of the GaN substrate 20. As a result, in the polishing step S110, the oxidation step S111 and the removal step S112 can be performed successively and alternately. That is, the oxidation step S111 can be performed when the first region 11 is in contact with the polished surface 14 of the GaN substrate 20, and the removal step S112 can be performed when the second region 12 is in contact with the polished surface 14 of the GaN substrate 20. In this specification, when a portion of the polished surface 14 is in contact with the first region 11 (for example, when the polished surface 14 is in contact with both the first region 11 and the second region 12), it is determined that the first region 11 is in contact with the polished surface 14 of the GaN substrate 20.
[0099] 11 is a graph showing a schematic diagram of a current flowing through the polishing pad 40 in the polishing step S110 of this embodiment. As shown in FIG. 11, in the polishing step S110 of this embodiment, even if a voltage is continuously applied, a current flows intermittently through the polishing pad 40, as in the first embodiment. Since the first region 11 is impregnated with Nafion 15 exhibiting electrical conductivity, a predetermined current flows through the polishing pad 40 when the first region 11 is in contact with the polished surface 14 of the GaN substrate 20 (oxidation step S111). On the other hand, since the second region 12 is not impregnated with a material exhibiting electrical conductivity such as Nafion 15, no current flows through the polishing pad 40 when the second region 12 is in contact with the polished surface 14 of the GaN substrate 20 (removal step S112).
[0100] 11, in the oxidation step S111 of this embodiment, the value of the current flowing through the polishing pad 40 changes depending on the area of the polished surface 14 in contact with the first region 11. From the viewpoint of controlling the current value to be constant and uniformly oxidizing the polished surface 14, it is preferable that the entire surface of the polishing surface 13 is impregnated with Nafion 15 as in the first embodiment described above.
[0101] (4) Effects of this embodiment According to this embodiment, one or more of the following advantages are achieved.
[0102] (a) The polishing pad 40 of this embodiment has a first region 11 on the polishing surface 13, which generates OH radicals and oxidizes the polished surface 14 of the GaN substrate 20 with the OH radicals, and a second region 12 which removes the oxides 31. Therefore, similar to the first embodiment, the polishing pad 40 can be used to oxidize and remove the oxides 31 from the polished surface 14 of the GaN substrate 20. As a result, it is possible to perform polishing while suppressing damage to the polished surface 14 of the GaN substrate 20.
[0103] (b) In the polishing pad 40 of this embodiment, the first region 11 and the second region 12 are arranged so as to alternately come into contact with the polished surface 14 of the GaN substrate 20 by relative movement between the polishing pad 40 and the GaN substrate 20. This allows the oxidation step S111 and the removal step S112 to be performed alternately in succession.
[0104] (c) In the polishing step S110 of this embodiment, since the region where the oxidation step S111 is performed (first region 11) and the region where the removal step S112 is performed (second region 12) are separated within the polishing surface 13 of the polishing pad 40, for example, in the oxidation step S111, the abrasive grains 32 do not come into contact with the polished surface 14 of the GaN substrate 20. This makes it possible to suppress the abrasive grains 32 from interfering with the oxidation of the polished surface 14 of the GaN substrate 20 in the oxidation step S111.
[0105] <Other embodiments of the present invention> Although the embodiment of the present invention has been specifically described above, the present invention is not limited to the above-mentioned embodiment, and various modifications can be made without departing from the gist of the present invention.
[0106] For example, in the above-mentioned second embodiment, a case where one sheet of nonwoven fabric is used to manufacture the polishing pad 40 has been described, but two or more sheets of nonwoven fabric may be used to manufacture the polishing pad 40. For example, Nafion 15 may be fixed to one nonwoven fabric and cerium oxide may be fixed to the other nonwoven fabric, and the respective nonwoven fabrics may be bonded together to manufacture the polishing pad 40 having the first region 11 and the second region 12 on the polishing surface 13.
[0107] Also, for example, in the above embodiment, the case where the GaN substrate 20 made of a single crystal of GaN is polished as the conductive semiconductor substrate has been described, but the conductive semiconductor substrate may be a III-nitride substrate made of a III-nitride other than GaN, such as InAlGaN, a silicon substrate made of a single crystal of silicon, or a SiC substrate made of a single crystal of silicon carbide (SiC). Also, for example, a template substrate in which a III-nitride is heteroepitaxially grown on an insulating substrate such as a sapphire substrate may be used. In this case, for example, the entire surface of the substrate can be polished by making contact from the side of the template substrate and applying a voltage. Among various conductive semiconductor substrates, it is very difficult to polish a GaN substrate at a practical polishing rate (for example, 100 nm / h or more), and therefore the present invention is particularly effective when polishing a GaN substrate.
[0108] Furthermore, for example, in the above embodiment, the case where the +c plane of the GaN substrate 20 is polished has been described, but the present invention is also applicable to polishing, for example, the -c plane, a-plane, m-plane, etc. of the GaN substrate 20.
[0109] Furthermore, for example, in the above-described first embodiment, a pulse voltage is applied to the polishing pad 10, but a voltage may be applied to the polishing pad 10 continuously.
[0110] In the above embodiment, for example, the case where OH radicals are generated and the polished surface 14 is oxidized has been described, but radicals other than OH radicals, atomic oxygen, etc. may be generated to oxidize the polished surface 14. For example, peroxodisulfate ions (SO 2- ) is supplied to the first region 11, and the peroxodisulfate ions are heated or irradiated with light to generate sulfate ion radicals (SO - By generating sulfate ion radicals, it becomes possible to oxidize the polished surface 14, as in the above-described embodiment.
[0111] In addition, for example, in the above embodiment, the case where pure water is supplied in a spray form using the pure water supply unit 24 has been described, but the manner in which pure water is supplied to the polishing surface 13 is not limited to the above embodiment. For example, gauze or the like soaked in pure water may be brought into contact with the polishing surface 13, and the pure water may be supplied to the polishing surface 13 by capillary action. In this case, it is easy to keep the humidity of the polishing surface 13 constant. EXAMPLES
[0112] Next, examples of the present invention will be described. These examples are merely examples of the present invention, and the present invention is not limited to these examples.
[0113] <Example 1> (1) Preparation of GaN Substrate 20 First, a plurality of GaN substrates 20 (diameter 2 inches) before polishing the surface 14 (+c surface) were prepared as conductive semiconductor substrates, and these were designated as samples 1 to 3. The carrier concentration of sample 1 was 1.6×10 17 cm -3 The carrier concentration of sample 2 and sample 3 was 2.56×10 18 cm -3 It was.
[0114] (2) Polishing of the GaN substrate 20 Using the polishing pad 40 described in the second embodiment of the present invention, the surface 14 to be polished of the sample 1 was polished while a voltage was continuously applied. The polishing conditions were as follows. Voltage (voltage applied by power supply 23): 100V Polishing pressure (pressure for pressing the polished surface 14 against the polishing surface 13): 18.3 kPa Rotation speed of the surface plate (rotation speed of the surface plate 21): 60 rpm Substrate rotation speed (rotation speed of the substrate holder 22): 60 rpm Polishing time (time to perform polishing process S110): 30 minutes (10 minutes x 3 times)
[0115] Moreover, the polishing surface 14 of the sample 2 was polished using the polishing pad 10 described in the first embodiment of the present invention while applying a pulse voltage. The polishing conditions were as follows. Voltage (voltage applied by power supply 23): 100V Duty ratio D: 5% Pulse period T: 40 seconds Polishing pressure (pressure for pressing the polished surface 14 against the polishing surface 13): 18.3 kPa Rotation speed of the surface plate (rotation speed of the surface plate 21): 120 rpm Substrate rotation speed (rotation speed of the substrate holder 22): 120 rpm Polishing time (time to perform polishing process S110): 30 minutes (10 minutes x 3 times)
[0116] For comparison, the polished surface 14 of the sample 3 was polished using a polishing pad in which only cerium oxide was dispersed in a nonwoven fabric without applying a voltage. The polishing conditions were as follows. Polishing pressure (pressure for pressing the polished surface 14 against the polishing surface 13): 18.3 kPa Rotation speed of the surface plate (rotation speed of the surface plate 21): 120 rpm Substrate rotation speed (rotation speed of the substrate holder 22): 120 rpm Polishing time (time to perform polishing process S110): 30 minutes (10 minutes x 3 times)
[0117] (3) Evaluation of polishing rate The polishing rate was calculated by measuring the weight and thickness of the GaN substrate 20 before and after polishing. The polishing rate of the sample 1 polished using the polishing pad 40 was 132 nm / h. From the above, it was confirmed that the polishing rate can be increased to 100 nm / h or more by polishing the polished surface 14 of the GaN substrate 20 using the polishing pad 40.
[0118] 12 shows the polishing amount (thickness removed by polishing) of sample 2 and sample 3. The polishing amount of sample 2 polished with polishing pad 10 was larger than that of sample 3 polished with a polishing pad having only cerium oxide fixed thereto. From the above, it was confirmed that the polishing rate can be improved by polishing surface 14 (+c surface) of GaN substrate 20 with polishing pad 10.
[0119] (4) Evaluation of surface roughness FIG. 13 shows the results of measuring the arithmetic mean roughness Ra of sample 1 before and after polishing using an optical surface texture measuring device (Zygo NewView 7300). The arithmetic mean roughness Ra before polishing was 1.39 nm. The arithmetic mean roughness Ra after 10 minutes of polishing was 1.06 nm. The arithmetic mean roughness Ra after 20 minutes of polishing was 0.840 nm. The arithmetic mean roughness Ra after 30 minutes of polishing was 0.687 nm. From the above, it was confirmed that by using the polishing pad 40 to polish the polished surface 14 of the GaN substrate 20, a GaN substrate 20 having a surface arithmetic mean roughness Ra of 0.7 nm or less can be manufactured.
[0120] <Example 2> (1) Preparation of the polishing pad 10 First, the polishing pad 10 was prepared according to the following procedure.
[0121] A nonwoven fabric with a diameter of 200 mm and an apparent thickness of 1 mm (apparent volume: 31.4 cm 3 The mass of the nonwoven fabric was 2.80 g.
[0122] The nonwoven fabric was impregnated with a cerium oxide dispersion liquid to which a small amount of sodium alginate had been added. The nonwoven fabric was then placed in an aqueous calcium chloride solution, and excess liquid was removed from the nonwoven fabric using a squeezer. The nonwoven fabric was then dried at 70°C for 30 minutes using a constant temperature dryer. The mass of the nonwoven fabric after drying was 23.88g. The increase in mass was 20.58g, and since 40% by mass of the increase was cerium oxide (the remaining 60% by mass was sodium alginate), the density of the abrasive grains 32 was 0.26g / cm 3 It was.
[0123] Next, the nonwoven fabric was impregnated with the Nafion dispersion, and excess liquid was removed from the nonwoven fabric using a squeezer. The nonwoven fabric was then dried at 70°C for 30 minutes using a constant temperature dryer. The mass of the nonwoven fabric after drying was 23.53g. The mass increase was 0.15g, and the density of Nafion 15 was 4.8mg / cm 3 It was.
[0124] (2) Polishing of the GaN substrate 20 and the SiC substrate A GaN substrate 20 and a SiC substrate were polished using the polishing pad 10 produced in (1). The GaN substrate 20 was prepared to be 2 inches in diameter, n-type, with the polished surface 14 being the +c-plane. The SiC substrate was prepared to be 4H—SiC, 2 inches in diameter, n-type, with the polished surface 14 being the Si-plane.
[0125] The polishing conditions were as follows: Voltage (voltage applied by power supply 23): 40V Current value: 100~150mA Duty ratio D: 90% Pulse period T: 120 seconds Polishing pressure (pressure for pressing the polished surface 14 against the polishing surface 13): 12 kPa Rotation speed of the surface plate (rotation speed of the surface plate 21): 60 rpm Substrate rotation speed (rotation speed of the substrate holder 22): 60 rpm Water supply amount: 0.4mL / min Temperature:RT Polishing time (time to perform polishing step S110): 10 minutes
[0126] (3) Evaluation of polishing rate The polishing rate was calculated by measuring the weight and thickness of the GaN substrate 20 and the SiC substrate before and after polishing. The polishing rate of the GaN substrate 20 was 1 μm / h. In other words, it was confirmed that the polishing rate when the GaN substrate 20 was polished using the polishing pad 10 under the above polishing conditions was 1 μm / h or more.
[0127] The polishing rate of the SiC substrate was 4.5 μm / h. In other words, it was confirmed that the polishing rate when polishing a SiC substrate using the polishing pad 10 under the above polishing conditions was 4.5 μm / h or more.
[0128] <Preferred embodiment of the present invention> Preferred embodiments of the present invention will be described below.
[0129] (Appendix 1) According to one aspect of the present invention, A polishing pad used for polishing a surface of a conductive semiconductor substrate, comprising: There is provided a polishing pad, the polishing surface which comes into contact with the surface to be polished being impregnated with at least a solid polymer electrolyte.
[0130] (Appendix 2) 2. The polishing pad according to claim 1, The solid polymer electrolyte is also impregnated in the polishing pad in the thickness direction.
[0131] (Appendix 3) A polishing pad according to claim 1 or 2, The solid polymer electrolyte has a density of 3 mg / cm 3 More than 20mg / cm 3 It is impregnated with the following densities:
[0132] (Appendix 4) A polishing pad according to any one of claims 1 to 3, With water molecules in contact with the solid polymer electrolyte, electrical continuity is established between the polished surface and the back surface opposite to the polished surface.
[0133] (Appendix 5) A polishing pad according to any one of claims 1 to 4, The polishing pad comprises a nonwoven fabric, The solid polymer electrolyte is attached to the surface of the fibers of the nonwoven fabric.
[0134] (Appendix 6) A polishing pad according to any one of claims 1 to 5, The solid polymer electrolyte is a polymer (Nafion) having a fluorocarbon skeleton and a fluorocarbon ether side chain having a sulfonic acid group at its end.
[0135] (Appendix 7) 7. The polishing pad according to claim 1, A conductive adhesive is applied to the back surface opposite the polished surface.
[0136] (Appendix 8) 8. A polishing pad according to any one of claims 1 to 7, Abrasive grains are dispersed on the polishing surface. Preferably, the abrasive grains have a hardness lower than that of the semiconductor crystals that constitute the surface to be polished.
[0137] (Appendix 9) 9. The polishing pad according to claim 8, The abrasive grains include cerium oxide, The abrasive grains have a density of 0.1 g / cm 3 More than 0.5g / cm 3 It is distributed at the following density:
[0138] (Appendix 10) 10. The polishing pad according to claim 8 or 9, The solid polymer electrolyte is attached to the surface of the abrasive grain.
[0139] (Appendix 11) 11. The polishing pad according to claim 8, When a gallium nitride substrate made of a single crystal of gallium nitride is polished while a voltage of 40 V is intermittently applied between the polishing pad and the gallium nitride substrate, the polishing rate is 1 μm / h or more. Preferably, the value of the current flowing through the gallium nitride substrate is not less than 100 mA and not more than 150 mA. Preferably, the duty ratio D is 90%. Preferably, the period T of the pulses is 120 seconds. Preferably, the pressure with which the polished surface is pressed against the polished surface is 12 kPa. Preferably, the rotation speed of the polishing pad and the gallium nitride substrate is 60 rpm. Preferably, the amount of water supplied to the polishing surface is 0.4 mL / min.
[0140] (Appendix 12) 12. The polishing pad according to any one of claims 8 to 11, When a silicon carbide substrate made of single crystal silicon carbide is polished while a voltage of 40 V is intermittently applied between the polishing pad and the silicon carbide, the polishing rate is 4.5 μm / h or more. Preferably, a value of a current flowing through the silicon carbide substrate is not less than 100 mA and not more than 150 mA. Preferably, the duty ratio D is 90%. Preferably, the period T of the pulses is 120 seconds. Preferably, the pressure with which the polished surface is pressed against the polished surface is 12 kPa. Preferably, the rotation speed of the polishing pad and the silicon carbide substrate is 60 rpm. Preferably, the amount of water supplied to the polishing surface is 0.4 mL / min.
[0141] (Appendix 13) According to another aspect of the present invention, A step of preparing a polishing pad, the polishing surface of which contacts the surface to be polished of the conductive semiconductor substrate being impregnated with at least a solid polymer electrolyte; a step of bringing the polishing surface of the polishing pad into contact with the surface to be polished of the conductive semiconductor substrate under pressure while water molecules are in contact with the solid polymer electrolyte, and polishing the surface to be polished by moving the polishing pad and the conductive semiconductor substrate relative to each other while applying a voltage between the polishing pad and the conductive semiconductor substrate; A method for manufacturing a conductive semiconductor substrate is provided, comprising:
[0142] (Appendix 14) A method for producing a conductive semiconductor substrate according to claim 13, comprising the steps of: In the polishing step, the surface to be polished is oxidized while the voltage is being applied.
[0143] (Appendix 15) A method for producing a conductive semiconductor substrate according to claim 13 or 14, comprising the steps of: In the polishing step, the voltage is applied intermittently.
[0144] (Appendix 16) A method for producing a conductive semiconductor substrate according to any one of claims 13 to 15, comprising: In the polishing step, a slurry containing abrasive grains is supplied to the polishing surface.
[0145] (Appendix 17) A method for producing a conductive semiconductor substrate according to any one of claims 13 to 16, comprising: In the polishing step, a porous structure is formed on the surface to be polished of the conductive semiconductor substrate, and then the porous structure is removed. Preferably, the conductive semiconductor substrate is a gallium nitride substrate made of a single crystal of gallium nitride.
[0146] (Appendix 18) A method for producing a conductive semiconductor substrate according to any one of claims 13 to 17, comprising: In the polishing step, a voltage V applied between the polishing pad and the conductive semiconductor substrate is controlled so as not to exceed a voltage Vm at which the polishing rate of the conductive semiconductor substrate is maximized. Preferably, the conductive semiconductor substrate is a silicon carbide substrate made of a single crystal of silicon carbide.
[0147] (Appendix 19) A method for producing a conductive semiconductor substrate according to any one of claims 13 to 18, comprising: In the polishing step, the polishing pad and the conductive semiconductor substrate are moved relative to each other for a predetermined time without applying a voltage between the polishing pad and the conductive semiconductor substrate, and then the polishing step is terminated.
[0148] (Appendix 20) According to another aspect of the present invention, A polishing pad for use in polishing a surface of a conductive semiconductor substrate, comprising: On a surface in contact with the surface of the conductive semiconductor substrate, a first region for generating radicals and oxidizing a semiconductor crystal constituting the surface of the conductive semiconductor substrate by the radicals; and a second region that removes oxides produced when the semiconductor crystal is oxidized by the radicals. Preferably, the polishing pad has water retention properties. Preferably, the surface of the polishing pad which comes into contact with the surface of the conductive semiconductor substrate has slidability relative to the surface of the conductive semiconductor substrate. Preferably, the polishing pad has a conductive adhesive on the back surface.
[0149] (Appendix 21) 21. The polishing pad according to claim 20, The radical is an OH radical.
[0150] (Appendix 22) 22. The polishing pad according to claim 20 or 21, The first region is impregnated with a solid polymer electrolyte that generates the radicals (from water upon application of a voltage). Preferably, the solid polymer electrolyte is impregnated throughout the entire polishing pad in the thickness direction. Preferably, the voltage is greater than or equal to 20V and less than or equal to 300V.
[0151] (Appendix 23) 23. The polishing pad according to any one of claims 20 to 22, Abrasive grains for removing the oxides are dispersed in the second region. Preferably, the abrasive grains have a hardness lower than that of the semiconductor crystals.
[0152] (Appendix 24) 24. The polishing pad according to any one of claims 20 to 23, The first region and the second region are arranged so as to alternately come into contact with the conductive semiconductor substrate by relative movement between the polishing pad and the conductive semiconductor substrate.
[0153] (Appendix 25) According to another aspect of the present invention, A polishing pad for use in polishing a surface of a conductive semiconductor substrate, comprising: Abrasive grains with a lower hardness than gallium nitride are dispersed in the material. There is provided a polishing pad having a polishing rate of 100 nm / h or more and 10,000 nm / h or less when polishing (the +c plane of) a gallium nitride substrate made of a single crystal of gallium nitride in a neutral region. Preferably, a voltage is applied to generate OH radicals from water, and the gallium nitride is oxidized by the OH radicals. Preferably, gallium oxide produced by oxidizing the gallium nitride is removed. Preferably, the voltage is greater than or equal to 20V and less than or equal to 300V. Preferably, the carrier concentration at the surface of the gallium nitride substrate is 1.0×10 16 cm-3 Above 1.0×10 20 cm -3 The following is the result.
[0154] (Appendix 26) According to another aspect of the present invention, A method for manufacturing a conductive semiconductor substrate, comprising the steps of: generating radicals and oxidizing semiconductor crystals constituting the surface of the conductive semiconductor substrate by the radicals; and removing an oxide produced by oxidizing the semiconductor crystal with the radicals, There is provided a method for manufacturing a conductive semiconductor substrate, in which the oxidizing step and the removing step are carried out by relatively moving a polishing pad that polishes the surface of the conductive semiconductor substrate and the conductive semiconductor substrate. Preferably, the oxidizing step and the removing step are carried out simultaneously or alternately. [Explanation of symbols]
[0155] 10 Polishing Pad 11 First area 12 Second area 13 Polished surface 14 Surface to be polished 15 Nafion 16. Textiles 17 Bubbles 18 Porous Layer 20 GaN substrate 21 Fixed Plate 22 Substrate holder 23 Power supply 24 Pure water supply section 30 GaN 31 Oxides 32 Abrasive grain 40 Polishing Pad S100 Preparation process S110 Polishing process S111 Oxidation process S112 Removal process
Claims
1. A polishing pad used for polishing a surface of a conductive semiconductor substrate, comprising: the polishing surface in contact with the surface to be polished is impregnated with at least a solid polymer electrolyte at a density of 3 mg / cm 3 or more and 20 mg / cm 3 or less; the substrate having the polishing surface has an open-cell structure, The solid polymer electrolyte covers at least a portion of the surface of the substrate.
2. 2. The polishing pad according to claim 1, wherein the solid polymer electrolyte is also impregnated in the thickness direction of the polishing pad.
3. A polishing pad as described in claim 1 or claim 2, wherein the solid polymer electrolyte covers and connects the inside of the air bubbles of the substrate.
4. 4. The polishing pad according to claim 1, wherein the polishing surface and the back surface opposite the polishing surface are electrically conductive when water molecules are in contact with the solid polymer electrolyte.
5. 5. The polishing pad according to claim 1, wherein the solid polymer electrolyte is a polymer having a fluorocarbon skeleton and a fluorocarbon ether side chain having a sulfonic acid group at its terminal.
6. 6. The polishing pad according to claim 1, further comprising a conductive adhesive on a back surface opposite to the polishing surface.
7. 7. The polishing pad according to claim 1, wherein abrasive grains are dispersed on the polishing surface.
8. 8. The polishing pad according to claim 7, wherein the solid polymer electrolyte is attached to the surfaces of the abrasive grains.
9. The polishing surface has at least a first region in which a solid polymer electrolyte is impregnated at a density of 3 mg / cm 3 to 20 mg / cm 3 , and a second region in which abrasive grains are dispersed; 9. The polishing pad according to claim 1, wherein the first region and the second region are arranged to alternately contact the polished surface due to relative movement between the polishing pad and the conductive semiconductor substrate.
Citation Information
Patent Citations
Ion exchange material for chemical-mechanical polishing
JP2001311073A
Catalyst-assisted chemical processing method
JP2006114632A
Wet processing apparatus
JP2006231130A
Polishing device
JP2006231517A
Electrical process profile control
JP2008528308A